2011
DOI: 10.1261/rna.2878711
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional role of bases 32 and 33 in the anticodon loop of yeast mitochondrial tRNAIle

Abstract: Previous work has demonstrated the usefulness of the yeast model to investigate the molecular mechanisms underlying defects due to base substitutions in mitochondrial tRNA genes, and to identify suppressing molecules endowed with potential clinical relevance. The present paper extends these investigations to two human equivalent yeast mutations located at positions 32 and 33 in the anticodon loop of tRNA Ile . Notwithstanding the proximity of the two T>C base substitutions, the effects of these mutations have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Regulation in replication, transcription and translation can play a major role in rapid adaptive evolution (Wittenhagen & Kelley 2003;Burton & Barreto 2012;Bailey et al 2014). Transfer RNA mutations in anticodon stem/loops might disrupt secondary structure and change function (Wittenhagen & Kelley 2003;Montanari et al 2011). Our results show such mutations in E. australis.…”
Section: Alternative Targets For Selectionmentioning
confidence: 63%
See 1 more Smart Citation
“…Regulation in replication, transcription and translation can play a major role in rapid adaptive evolution (Wittenhagen & Kelley 2003;Burton & Barreto 2012;Bailey et al 2014). Transfer RNA mutations in anticodon stem/loops might disrupt secondary structure and change function (Wittenhagen & Kelley 2003;Montanari et al 2011). Our results show such mutations in E. australis.…”
Section: Alternative Targets For Selectionmentioning
confidence: 63%
“…Transfer RNA mutations in anticodon stem/loops might disrupt secondary structure and change function (Wittenhagen & Kelley ; Montanari et al . ). Our results show such mutations in E. australis .…”
Section: Discussionmentioning
confidence: 97%
“…Laboratory yeast strains are genetically and physiologically heterogeneous, with differences in growth behaviours (Montanari et al, 2008; 2011; De Luca et al, 2006; 2009). W303-1A has been selected in French laboratories due to its good sporulation and formation of complete tetrads, which is useful for genetic analysis in which high respiration is necessary.…”
Section: Resultsmentioning
confidence: 99%
“…In the course of our studies on mt tRNA mutants (De Luca et al 2009 ; Montanari et al 2010 , 2011 ), we have previously observed important phenotypic differences among S. cerevisiae strains, indicating that a better definition of the involved genetic variability will be essential to define the relationship between the mt efficiency and the characteristics of different nuclear backgrounds.…”
Section: Introductionmentioning
confidence: 93%